Pengaruh Kualitas Pelayanan (Reliability, Assurance, Tangible, Empathy, Dan Responsiveness) terhadap Kepuasan Nasabah pada Bank Kalteng Cabang Muara Teweh - M. Solichin; Rasyidi Rasyidi; Siti Halimatusa’diah (JURNAL BISNIS DAN PEMBANGUNAN, 2019)
Research this aim for test influence Reliability (X1), Assurance (X2), Tangible (X3), Emphathy (X4) and Responsiveness (X5) on Customer satisfaction at Bank Kalteng Caang Muara Teweh. Sample taken as much 98 Selected customers with formula Slovin. Collecting data using questionnaire while data analysis using SPSS. Results testing prove Reliability effect significant to Customer's Decision on Partial with big influence 31.1%, an effect Assurance significant to Customer satisfaction on Partial with big influence 11.8% Tangible effect significant to Customer satisfaction on Partial with big influence 3.5%, Emphathy take effect significant to Customer satisfaction on Partial with big influence 2.7%, Responsiveness effect significant to Customer satisfaction on Partial with big influence Whereas 50.2% on simultaneously Reliability, Assurance, Tangible, Emphathy and Responsiveness take effect significant to Customer satisfaction with big influence 42.1% while the rest amount 57.9% influenced by other variables Keywords:    Reliability, Assurance, Tangible, Empathy, Responsiveness, Customer Satisfaction